Production of Historical Works in Ethiopia and Eritrea. Some Notes on the State of Recent Publications 1991-97 - Tafla, Bairu (Aethiopica, 1998)
As the random samples in the preceding notes show, publications of various kinds and qualities have been continuously produced (albeit obvious financial, political and technical difficulties) in Ethiopia and Eritrea in Amharic, English, Gǝʿǝz, and Tǝgrǝñña throughout the decades of this century, and particularly in the present one. In the field of history, which has been taken as a point of focus in this article, conspicuous progress seems to have been made in the last half a dozen or so years as a result of the enhancement of historical consciousness promoted partly through education and partly through the prevailing political circumstances which awakened many, at least in the case of Ethiopia, to the uncertainties that have been looming up on the horizon. In the case of Eritrea, the primary drive seems to have been the search for identity and self-assertion following the attainment of sovereignty. Another factor is the rise of a relatively vast and rapacious readership in both countries evolving from the educational efforts of the last half of a century and the general literacy campaign which accompanied formal schooling. Furthermore, there has been a marked expansion of printing facilities, bookshops and libraries, as well as some pioneering publishing houses – all of which might have provided an impetus in their own way. The production of some works critical of the contemporary government may also reflect the existence of a relative relaxation in censorship, at least in the early years of the decade, a unique situation which was unthinkable under the monarchy and the Marxist regime. Two significant aspects of the recent production of historical works in Ethiopia and Eritrea have been the marked improvement in quality as well as the increase in thematic variety. Episodic, epochal, biographical and autobiographical studies are prevailing over the traditional tendency of commencing history with Adam and Eve. Likewise, the narrative and/or collective method of history is gradually giving way to the interpretive, but not at the expense of source materials which are also being sought, collected and published. Most of the works have a touch of originality, as they incorporate, consciously or otherwise, materials derived from oral traditions and personal observations of the authors. It is, therefore, time for scholars, reviewers, bibliographers and librarians outside those countries to take these works seriously into account.